Neuroinflammation aggravated by traumatic brain injury at high altitude is reversed by L-serine via NFAT1-mediated microglial polarization - Liu, Jinchun; Peng, Shunhua; Ye, Lisha; Sun, Yechao; Zhao, Qiong; Wei, Hua; Luo, Qianqian; He, Min; Wang, Guohua (Frontiers in Cellular Neuroscience, 2023)
Traumatic brain injury (TBI) is one of the main causes of death and disability, especially in plateau areas, where the degree of injury is often more serious than in plain areas. It is likely that high altitude (HA) aggravates neuroinflammation; however, prior studies are limited. This study was designed to evaluate the effects of HA on the degree of TBI, the neuroprotective effect of L-serine and the underlying mechanisms against TBI at HA (HA-TBI). In in vivo experiments, wild-type mice and mice deficient in the gene Nfat1 (Nfat1-/-) in the C57BL/6 background were kept in a hypobaric chamber for 3 days under simulated conditions of 4,000 m, 6,000 m and 8,000 m above sea level. After leaving the chamber, the standardized TBI model was established immediately. Mice were then intraperitoneally injected with L-serine (342 mg/kg) 2 h after TBI and then daily for the next five days. Behavioral tests and histological analysis were assessed at different time points post TBI induction. In vitro, we applied primary cultured microglia for hypoxia treatment (1% O2 for 24 h). The major findings include the following: 1) with increasing altitude, the neurological function of TBI mice decreased, and the damage to cerebral gray matter and white matter became more significant; 2) L-serine significantly improved the sensorimotor function of mice, reversed the increase in brain lesion volume, and promoted the renovation of brain tissue after HA-TBI; 3) L-serine significantly decreased the activation of microglia and shifted microglia polarization toward the protective M2 phenotype both in vivo and in vitro; 4) L-serine significantly inhibited the expression of NFAT1 in mice after HA-TBI and significantly inhibited the expression of NFAT1 in primary microglia; and 5) knockout of Nfat1 inhibited the inflammatory reaction caused by excessive activation of microglia, and L-serine lost its neuroprotective effect in Nfat1 knockout mice. The present study suggests that HA aggravates brain damage after TBI and that the damage also increases with increasing altitude. As an endogenous amino acid, L-serine may be a neuroprotective agent against HA-TBI, and inhibition of NFAT1 in microglia is a potential future therapy for neuroinflammation.